Effect of Chitosan on Morphological Change Of Colletotrichum capsici (Sydow) Butler & Bisby - Paristiyanti Nurwardani (Fakultas Sains Terapan, Universitas Suryakancana Cianjur, 2011)
Worldwide, postharvest losseshave been estimated at 50% andmuch of this is due to fungal andbacterial infection. One of theimportant funguses that attack thepostharvest product is fungusColletotrichum capsici (Sydow)Butler & Bisby. This funguscaused anthracnose disease (Figure1 and 2).The symptom of anthracnose isblack lesion, usually sunken causedby imperfect fungi that produceconidia in ecervuli. Conidia areborne on acervuli, witch areerumpent, cushion-like masses ofconidiophores. The conidia arehyaline, one celled, avoid tooblong. The mycelium ofpathogen is septate , inter-andintracellular. Acervuli and stromain the stem are hemispherical and70-120 μ in diameter. Setae arescattered and dark brown. Thetips are light brown and severalseptate and up to 150 μ in length.Conidiophores are aseptate andunbranched. Conidia in massappear light pinkish in color.Conidia are borne singly at the tipsof the conidiophores. Individuallythey are hyaline, unicellular andcaved with narrowed ends. Thesemeasure 7-28 x 3-4 μ. This is thecharacteristic oil globule in thecenter of each conidium. Conidiagerminate in water within fourhours. The germ tube soon formsan appressorium (Mehrorta, 1980).